Hippocampus-dependent cognitive enhancement induced by systemic gintonin administration - Sungmin Kim; Min-Soo Kim; Kwanghoon Park; Hyeon-Joong Kim; Seok-Won Jung; Seung-Yeol Nah; Jung-Soo Han; ChiHye Chung (Journal of Ginseng Research, 2016)
Background: A number of neurological and neurodegenerative diseases share impaired cognition as a common symptom. Therefore, the development of clinically applicable therapies to enhance cognition has yielded significant interest. Previously, we have shown that activation of lysophosphatidic acid receptors (LPARs) via gintonin application potentiates synaptic transmission by the blockade of K+ channels in the mature hippocampus. However, whether gintonin may exert any beneficial impact directly on cognition at the neural circuitry level and the behavioral level has not been investigated. Methods: In the current study, we took advantage of gintonin, a novel LPAR agonist, to investigate the effect of gintonin-mediated LPAR activation on cognitive performances. Hippocampus-dependent fear memory test, synaptic plasticity in the hippocampal brain slices, and quantitative analysis on synaptic plasticity-related proteins were used. Results: Daily oral administration of gintonin for 1 wk significantly improved fear memory retention in the contextual fear-conditioning test in mice. We also found that oral administration of gintonin for 1 wk increased the expression of learning and memory-related proteins such as phosphorylated cyclic adenosine monophosphate-response element binding (CREB) protein and brain-derived neurotrophic factor (BDNF). In addition, prolonged gintonin administration enhanced long-term potentiation in the hippocampus. Conclusion: Our observations suggest that the systemic gintonin administration could successfully improve contextual memory formation at the molecular and synaptic levels as well as the behavioral level. Therefore, oral administration of gintonin may serve as an effective noninvasive, nonsurgical method of enhancing cognitive functions.